Analysis of Activity Based Costing (ABC) Calculations in Services Hemodialysis at the Kudungga Regional Hospital Dialysis Unit - Dwi Astuti Noor Wijayanti; Ratno Adrianto; Iwan Muhammad Ramdam; Irfansyah Baharuddin Pakki; Iriyani Kamaruddin; Rahmat Bahtiar (GLOBAL HEALTH SCIENCE GROUP, 2025)
Hemodialysis is a kidney replacement therapy where blood from outside the body is filtered by a machine. The provision of hemodialysis services currently still uses the old rates and is considered not to provide profits for hospitals, so good calculations are needed as a form of efficiency in financing hemodialysis procedures in hospitals, especially in the JKN era. Hospitals will receive comprehensive information on shopping costs, unit cost calculations and action suggestions in accordance with applicable rates. The study was carried out with the aim of finding out the unit cost rates for hemodialysis services in the Kudungga Regional Hospital Dialysis Unit using the Activity Based Costing (ABC) method and comparing them with INA-CBGs rates and hospital rates. This research uses a descriptive and quantitative approach. Unit costs for dialysis units and cost analysis using the Activity Based Costing (ABC) method approach are the main subjects of this research. This research is based on all financial balance data for hemodialysis services at the Kudungga Regional Hospital Dialysis Unit. The unit cost of hemodialysis can be determined by tracing the costs related to the hemodialysis cost center as a production center and other elements that support this action. The data will be grouped into fixed costs, semi-variable costs and variable costs, then included in direct costs, indirect costs, overhead and unit cost calculations using the Activity Based Costing (ABC) method. The research results show that the unit cost calculation for hemodialysis based on the Activity Based Costing (ABC) method is IDR 1,397,627.79. Meanwhile, the Kudungga Regional Hospital rate is only IDR 1,258,300, the hospital rate only meets 90.03% of the unit cost using the ABC method. Meanwhile, when compared with the INA-CBGs tariff, which is IDR 921,300, the INA-CBGs tariff only meets 65.92% of the unit cost using the ABC method. Things that influence are direct costs, indirect costs and the number of hemodialysis procedures.